The Determinants of Foreign Direct Investment in Vietnam: Gravity Model Approach - Ngoc Minh, Ngo (International Journal of Psychosocial Rehabilitation, 2020)
The paper employs the gravity model to investigate determinants affecting foreign direct investment (FDI) attraction to Vietnam based on panel data from 10 biggest FDI partners of Vietnam for the period of 2005-2019. By using pooled ordinary least square (OLS), random effect (RE), and fixed effect (FE) models, the empirical results show that the geographical distance, gross domestic product (GDP), gross domestic product per capita (GDP per capita), trade openness, and labor costs significantly impact FDI attraction. These results offer an insight to suggest some policy implications that will help promote more FDI inflows into Vietnam in the future.